Preliminary evidence of prolonged timing effects of theta-burst stimulation in the reading system - Harrington, Rachael M.; Krishnamurthy, Lisa C.; Ossowski, Alexandra; Jeter, Mykayla; Davis, Adriane; Bledniak, Ewelina; Ware, Ashley L.; Morris, Robin; Arrington, C. Nikki (Frontiers in Human Neuroscience, 2023)
Theta-burst stimulation (TBS) is a repetitive transcranial magnetic stimulation technique that can be used to upregulate or downregulate different brain regions. However, the timing of its effects and the differing effects of continuous TBS (cTBS) versus intermittent TBS (iTBS) in the reading system have not been explored. This study assessed how stimulation type and post-stimulation timing affected change in performance during a phonological discrimination and sight word recognition task after stimulation of supramarginal gyrus (SMG). Fourteen right-handed young adults (age 18–27 years; 44% male) were block-randomized to receive either iTBS or cTBS to the supramarginal gyrus. Participants then performed a pseudoword discrimination task and an orthographic awareness task (behavioral control) at four different time points and change in reaction time compared to baseline was measured from each time point. There was no effect of stimulation type on change in reaction time [t(16) = −0.2, p = 0.9], suggesting that both types of TBS caused similar effects. Percent change in reaction time decreased over time in the pseudoword task [t(50) = −5.9, p < 0.001], indicating faster pseudoword processing speed with better performance 60–70 min after stimulation. In contrast, no change was demonstrated over time for the behavioral control task [t(43) = −0.6, p = 0.6], suggesting that the change over time seen in the test condition was not a learning effect. These findings provide insight into the effects of TBS on the reading system and can guide future study designs.